Peran Kecerdasan Emosi dan Iklim Organisasi terhadap Perilaku Kerja Kontraproduktif - Devianita Puspita Wardhani; IJK Sito Meiyanto (Faculty of Psychology, Universitas Gadjah Mada, 2017)
This research aims to determine the role of emotional intelligence and organizational climate in predicting counterproductive work behavior. This study used a quantitative approach survey. The method of data collection in this research was conducted by distributing scale to the research subjects, with a total of 146 civil servants. The data was analyzed using double regression techniques using SPSS (Statistical Product and Service Solutions) 20.0. The result shows that the emotional intelligence and organizational climate can contribute together to decrease counterproductive behavior that occurs in the workplace (F (2, 143) = 5.266, p<.05, R2 = .069). Limitations and suggestions for further research were also discussed in this study.